2005
DOI: 10.1093/carcin/bgi359
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac regulates the aryl hydrocarbon receptor-mediated expression of Phase 1 metabolic enzymes in vivo and in vitro

Abstract: Sulindac, a widely used non-steroidal anti-inflammatory drug (NSAID), has been shown to inhibit chemically induced carcinogenesis in animal models. In the present study, we have investigated the molecular mechanism by which sulindac affects the activity and expression of the enzymes that mediate the initial detoxification steps of many environmental carcinogens, the cytochromes P450 1A1, 1A2 and 1B1. Sulindac treatment of Sprague-Dawley rats resulted in a dose-dependent increase in hepatic cytochrome P450 (CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…It has been shown to induce the expression of several P450 enzymes (39) and ubiquinone oxido/reductase, a marker for the Phase 2 system (40). Thus, the activity of sulindac as a chemoprotectant could involve a combination of activities, including antiinflammatory, cell preconditioning, and induction of Phase 1 and Phase 2 enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to induce the expression of several P450 enzymes (39) and ubiquinone oxido/reductase, a marker for the Phase 2 system (40). Thus, the activity of sulindac as a chemoprotectant could involve a combination of activities, including antiinflammatory, cell preconditioning, and induction of Phase 1 and Phase 2 enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Both cell lines are aggressive and represent subclasses of breast cancer that do not respond well to endocrine therapy but are growth-inhibited by TCDD and MCDF (Zhang et al, 2009). The pharmaceuticals (and their applications) include leflunomide (anti-inflammatory), flutamide (antiandrogen), nimodipine (calcium channel blocker), mexiletine (antiarrhythmic), and sulindac (anti-inflammatory), which induce CYP1A1 rodent systems (in vivo and in vitro) (Ciolino et al, 2006;Hu et al, 2007;O'Donnell et al, 2010); tranilast (antiallergic drug), which exhibits AHR agonist activity and inhibits breast cancer cell and stem cell growth (Prud'homme et al, 2010); 4-hydroxytamoxifen, which induces CYP1A1/ 1B1 in breast cancer cells and suppresses osteoclast differentiation (DuSell et al, 2010); and omeprazole (Quattrochi and Tukey, 1993;Dzeletovic et al, 1997;Hu et al, 2007), which also induces CYP1A1 and exhibits other AHR agonist activities. We investigated the effects of these pharmaceuticals on AHR expression, CYP1A1 (protein and mRNA), CYP1B1 mRNA and protein, and functional responses in MDA-MB-468 and BT474 cells and compared these effects with results for TCDD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that sulindac could induce several of the P450 enzymes that were regulated by the AHR (Ciolino et al, 2006(Ciolino et al, , 2008. These authors used ethoxyresorufin as a substrate to measure induction of the P450 system but did not measure the induction of the P450 enzymes that oxidize sulindac or the effect of the sulindac FIG.…”
Section: Sulindac Metabolites Detected In Normal Ratmentioning
confidence: 99%
“…It should be noted that the R-epimer is oxidized at a faster rate than the S-epimer, regardless of which epimer is used during the preincubation (induction) period. We assume that the sulindac epimers are inducing the P450 enzymes in these experiments because Ciolino et al (2006Ciolino et al ( , 2008 have clearly shown that sulindac and its metabolites can induce several P450 enzymes. However, we should stress that we have not directly shown that the P450 enzymes are induced, only that there is an increase in P450 enzymatic activity after the cells are exposed to sulindac over a 24-h period.…”
Section: With Either (R)-or (S)-sulindac After the Pretreatment Perimentioning
confidence: 99%
See 1 more Smart Citation